Dependence on visual information in patients with ACL injury for multi-joint coordination during single-leg squats: a case control study - Minoru Toriyama; Atsuo Nakamae; Takumi Abe; Kazuhiko Hirata; Nobuo Adachi (BMC, 2024)
Abstract Background The influence of vision on multi-joint control during dynamic tasks in anterior cruciate ligament (ACL) deficient patients is unknown. Thus, the purpose of this study was to establish a new method for quantifying neuromuscular control by focusing on the variability of multi-joint movement under conditions with different visual information and to determine the cutoff for potential biomarkers of injury risk in ACL deficient individuals. Methods Twenty-three ACL deficient patients and 23 healthy subjects participated in this study. They performed single-leg squats under two different conditions: open eyes (OE) and closed eyes (CE). Multi-joint coordination was calculated with the coupling angle of hip flexion, hip abduction and knee flexion. Non-linear analyses were performed on the coupling angle. Dependence on vision was compared between groups by calculating the CE/OE index for each variable. Cutoff values were calculated using ROC curves with ACL injury as the dependent variable and significant variables as independent variables. Results The sample entropy of the coupling angle was increased in all groups under the CE condition (P < 0.001). The CE/OE index of coupling angle variability during the descending phase was higher in ACL deficient limbs than in the limbs of healthy participants (P = 0.036). The CE/OE index of sample entropy was higher in the uninjured limbs of ACL deficient patients than in the limbs of healthy participants (P = 0.027). The cutoff value of the CE/OE index of sample entropy was calculated to be 1.477 (Sensitivity 0.957, specificity 0.478). Conclusion ACL deficient patients depended on vision to control multiple joint movements not only on the ACL deficient side but also on the uninjured side during single leg squat task. These findings underscore the importance of considering visual dependence in the assessment and rehabilitation of neuromuscular control in ACL deficient individuals.